2021
DOI: 10.7860/jcdr/2021/48607.15269
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Jacobson’s Progressive Muscle Relaxation on Stress Levels of Exam Going MBBS Students of a Medical College in South Gujarat, India

Abstract: Introduction: Academic examinations are a very stressful event for an Bachelor of Medicine and Bachelor of Surgery (MBBS) student. While many students learn to deal with it through the use of helpful or unhelpful coping skills, many still end up with considerable psychological morbidity in the form of anxiety and depression along with deterioration in overall health. Jacobson’s Progressive Muscle Relaxation (JPMR) causes deep muscle relaxation. Aim: To find out the prevalence of stress and exam anxiety in stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“… High 13 Mustafa et al 51 (2021) Pakistan 4 sessions/ 4 weeks N/A 10 female nurses (PMR: 10) S: N/A DO: 0% QED / / DASS-21 N/A Stress (d=2.45), anxiety (d=0.53), depression (d=1.95) There is a significant decrease (↓) in stress and depression score but not in anxiety at post-test compared to pretest in IG. High 14 Palkar et al 52 (2021) India 45m at home/ 4 weeks + 3 sessions at seminar hall 7 days/ week 114 medical students (PMR: 43, CG: 71) S: Seminar Hall & at home DO: 0% QED / / PSS, TAS N/A Stress (d=0.45), Anxiety (d=0.35) There is a significant decrease (↓) in stress and anxiety score at post-test compared to pretest in IG. High 15 Prakash Jha et al 53 (2020) India 30m/ 2 weeks 7 days/ week 30 elderlies (PMR: 30) S: N/A DO: 0% QED / / (twice) GDS N/A Depression There is a significant decrease (↓) in depression score at post-test compared to pretest.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… High 13 Mustafa et al 51 (2021) Pakistan 4 sessions/ 4 weeks N/A 10 female nurses (PMR: 10) S: N/A DO: 0% QED / / DASS-21 N/A Stress (d=2.45), anxiety (d=0.53), depression (d=1.95) There is a significant decrease (↓) in stress and depression score but not in anxiety at post-test compared to pretest in IG. High 14 Palkar et al 52 (2021) India 45m at home/ 4 weeks + 3 sessions at seminar hall 7 days/ week 114 medical students (PMR: 43, CG: 71) S: Seminar Hall & at home DO: 0% QED / / PSS, TAS N/A Stress (d=0.45), Anxiety (d=0.35) There is a significant decrease (↓) in stress and anxiety score at post-test compared to pretest in IG. High 15 Prakash Jha et al 53 (2020) India 30m/ 2 weeks 7 days/ week 30 elderlies (PMR: 30) S: N/A DO: 0% QED / / (twice) GDS N/A Depression There is a significant decrease (↓) in depression score at post-test compared to pretest.…”
Section: Methodsmentioning
confidence: 99%
“…Next, when anxiety outcomes were analyzed, seven (7) studies 42 , 44 , 50 , 52 , 56 , 69 , 71 reported a significant decrease in levels of anxiety among university students, and nurses at posttest compared to pretest in the PMR group, highlighting the effective role of PMR in anxiety reduction. Besides, two (2) further studies 36 , 56 supported the discussion for PMR by demonstrating a substantial reduction in anxiety outcomes among athletes, and nursing students in the PMR group compared to the control group in the posttest phase.…”
Section: Standalone Progressive Muscle Relaxation (Pmr) Studies Vs Pm...mentioning
confidence: 99%
See 2 more Smart Citations